Association between the serum glucose-to-potassium ratio and clinical outcomes in ischemic stroke patients after endovascular thrombectomy - Zhang, Qianqian; Huang, Zhihang; Chen, Shuaiyu; Yan, E.; Zhang, Xiaohao; Su, Mouxiao; Zhou, Junshan; Wang, Wei (Frontiers in Neurology, 2024)
Background and purpose The baseline glucose-to-potassium ratio (GPR) is associated with poor outcomes in patients with acute brain injury and intracranial hemorrhage. However, the impact of serum GPR on clinical outcomes after endovascular thrombectomy (EVT) is unclear. This study aimed to evaluate the association between the GPR at admission and functional outcomes at 90 days after EVT. Methods We retrospectively reviewed our database for patients with acute ischemic stroke involving an anterior circulation large-vessel occlusion who received EVT between October 2019 and December 2021. The baseline serum GPR was measured after admission. The primary outcome was a 90-day poor outcome, which was defined as a modified Rankin scale score of 3–6. Results A total of 273 patients (mean age, 70.9 ± 11.9 years; 161 men) were finally included for analyses. During the 90-day follow-up, 151 patients (55.3%) experienced an unfavorable outcome. After adjusting for demographic characteristics and other potential confounders, the increased GPR was significantly associated with a higher risk of a 90-day poor outcome (odds ratio, 1.852; 95% confidence interval, 1.276–2.688, p = 0.001). Similar results were observed when the GPR was analyzed as a categorical variable. In addition, the restricted cubic spline observed a positive and linear association between the GPR and poor outcomes at 90 days (p = 0.329 for linearity; p = 0.001 for linearity). Conclusion Our study found that ischemic stroke patients with the higher GPR at admission were more likely to have an unfavorable prognosis at 3 months, suggesting that GPR may be a potential prognostic biomarker for ischemic stroke after EVT.